Dengue death profile (2015-2023) in a São Paulo municipality: challenges for public health - Santos, Ezequiel Aparecido dos (2024)
In the first half of 2023, the number of dengue cases in the Americas surpassed the total for 2022, with Brazil leading the list with 2.3 million disease occurrences and 769 deaths. Dengue is expanding globally and is already considered endemic in more than 100 countries. This study characterizes the profile of dengue deaths from 2015 to 2023 in a municipality of São Paulo. A cross-sectional, retrospective, and descriptive study was conducted with secondary data obtained from the National Notification System (SINAN), Mortality System (SIM), and dengue death database of the municipal epidemiological surveillance mortality committee. Only in 42.9% of cases were the health teams able to identify the signs and symptoms before hospitalization and death, followed by after death (8.8%) and on the day of death (11.7%). Dengue mortality predominated among male individuals (51.4%) with a median age of 74 years. Data analysis showed that the clinical management of dengue remains challenging for health teams, who needs continuous training to recognize the signs and symptoms, warning signs, and severity for correct management of each case, aiming to reduce mortality.